Break Even Point Analysis as a Tool for Sales and Profit Planning: A Case Study of PT Ultrajaya Milk Industry & Trading Company Tbk. - Salsa Billa Hasfan; Muhammad Imam Sundarta; Denia Maulani (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2026)
Based on the results and discussions that have been presented in this study, PT. Ultrajaya Milk Industry & Trading Company, Tbk did not suffer a loss, it was concluded that the total production cost in 2020 was Rp. 15,185,422. The position of the BEP break-even point is at a nominal value of Rp. 14,780,337. The method used in this research is descriptive qualitative method. This method is a qualitative approach that describes conditions, situations, and variables. The purpose of this study is to analyze the Break Even Point of the company Ultrajaya Milk Industry Tbk, besides that this research will also explain the general description of sales planning and provide sales volume targets that must be generated at PT. Ultrajaya Milk Industry Tbk. The results of the company's research can plan sales in 2021 for Rp. 16,781,882, with a margin of safety or a safety limit of 37.43%. The minimum sales that must be made in 2021 are 1,049 units with a nominal value of Rp. 16,781,882. The weakness of BEP is that the selling price per unit does not stand alone regardless of sales volume. From the analysis of the break even point is the difficulty in classifying costs due to the existence of semi-variable costs so that sales made by PT.Ultrajaya Milk Industry & Trading Company, Tbk In accordance with the planning that has been done, the company must pay attention to the safety and sales limits that must be maintained by the company.